Sistem Pengendalian Banjir Sungai Aur di Kota Palembang - Amin, Muhammad; Syarifudin, Achmad (Jurnal Tekno, 2021)
Palembang is a metropolitan city in Indonesia and geographically located between 2o 52 ′ to 3o 5 ′ south latitude and 104o 37 ′ to 104o 52 ′ east longitude with an average height of 8 meters above sea level. The area of ​​Palembang City is 400.61 km2 which is administratively divided into 16 districts and 107 villages. Palembang City is the capital city of South Sumatra Province with territorial boundaries in the north, east and west with Banyuasin Regency; while the south is bordered by Muara Enim Regency. Musi River has 19 sub-watersheds, one of which is the Aur Sub-Basin which is the location of this research. This research method was carried out by means of a numerical approach with the help of the HECRAS 4.1 program and the discharge data was obtained through an empirical formula. The pattern of water flow movement from the Musi River towards the Aur River in the return period of 2, 5, 10, 20 and 50 years causes runoff and the volume of the existing retention pond exceeds the existing capacity. The mainstay discharge in the return period of 2, 5, 10, 20 and 50 years does not cause runoff on the Aur River with a flow time of 5 minutes. However, if it is more than that time, the retention pond storage capacity will overflow and cause flooding. The flow pattern in the channel leading to the Aur River is very small so that when the river water overflows it will slow down a decline. Along the Channel and Aur River there is a maximum overflow at STA 1 + 450 in the 2 year return period of 0.85 m ', in the 5 year return period of 1.16 m', the 10 year return period of 1.35 m ', in the return period 20 years is 1.58 m 'and in the 50 year return period it is 1.75 m'. The flood control system in the Aur River Basin consists of 2 (two) ways : technical and non technical methods